Risk Factors for Pregnancy Associated Venous Thromboembolism - McColl, Mark D; Ramsay, Jane E; Tait, R C; Walker, Isobel D; McCall, Frances; Conkie, J A; Carty, M J; Greer, I A (Thrombosis and Haemostasis, 1997)
In an attempt to reduce the incidence of pregnancy associated venous thromboembolism (PA-VTE), some researchers have advocated screening of all women for the factor VLeiden mutation during early pregnancy. We have conducted a large retrospective study (over 72,000 deliveries) to determine if this would be useful. Sixty-two objectively confirmed venous thrombotic events (51 DVT, 11 PE) were recorded at two maternity units in the UK. The incidence of DVT was 0.71 per 1000 deliveries (95% CI 0.5-0.9) with 0.50 occurring in the antenatal period (95% CI 0.34-0.66) and 0.21 in the puerperium (95% CI 0.11-0.31). The incidence of PE was 0.15 per 1000 deliveries (95% CI 0.06-0.24), 0.07 antenatal (95% CI 0.01-0.13) and 0.08 in the puerperium (95% CI 0.02-0.14). Of these 62,50 attended for follow-up and thrombophilia screening. 28% of all episodes of PA-VTE had no CIinical risk factor for thrombosis or an identifiable thrombophilic abnormality. Deficiency of antithrombin was identified in 12% of individuals (95% CI 3-21) and the factor VLeiden mutation in 8% (95% CI 0.5-15.5). Based on estimates of the prevalence of the factor VLeiden mutation in the population, we estimate that the thrombotic risk for a woman during pregnancy or the puerperium with the defect is approximately 1 in 400-500. This figure would not lend support to the idea of random screening for the mutation in early pregnancy.